Final report CATIE/AID Fourth International Short Course Agroforestry for the Humid Tropics: 24 April - 4 May 1984 - MAJOR, M. (CATIE, Turrialba (Costa Rica). Dept. de Recursos Naturales Renovables, 2014)
34 pág, tab